Construction and Transient Expression of Chimeric Cassettes Containing CaMV 35S or OsAER1 Promoter and GUS Gene Fusion in Tobacco - Apriana, Anniversari; Sisharmini, Atmitri; Awidinnoor, Hajrial; Trijatmiko, Kurniawan Rudi; Sudarsono, Sudarsono (Jurnal AgroBiogen, 2018)
Reporter gene assays are commonly used to study the expression pattern of a gene and the promoter activity. The purpose of this study was to assemble the chimeric gene constructs consisting of CaMV 35S promoter orOsAER1 gene promoter connected to the β-glucuronidase (GUS) reporter gene encoding the β-glucuronidase enzyme and to obtain an efficient method for Agrobacterium tumefaciens-mediated transient transformation of tobacco sprouts. The CaMV 35S promoter fragment reamplified from pCAMBIA1301 binary vector and the OsAER1 gene promoter fragment amplified from rice cv. Awan Kuning were ligated into pCAMBIA1300int::gus::tNOS to produce binary vectors pCAMBIA1300int::p35S::gus::tNOS and pCAMBIA1300int::prOsAER1::gus::tNOS. The vectors were used for transient transformation of 5–day old tobacco seedlings. The transformation was carried out using two bacterial cultures with densities of OD600 = 0.5 or OD600 = 1.0 combined with a vacuum for 15 or 30 minutes. Tobacco seedlings transformed with pCAMBIA1300int::p35S::gus::tNOS showed higher transformation efficiency as compared tothe ones transformed with pCAMBIA1300int::prOsAER1::gus::tNOS. A higher efficiency was obtained from transformation using bacterial culture with density of OD600 = 0.5 in combination with a vacuum for 30 minutes. Expression of GUS gene in the tobacco sprouts transformed with CaMV 35S promoter construct was observed through out the sprouts area (root, hypocotyl, cotyledon, and leaf), where as expression of GUS gene was observed in root, hypocotyl, and cotyledon, but not in leaf on tobacco sprouts transformed with OsAER1 promoter construct. These results indicate that the transient transformation is a quick and simple method for testing a chimeric gene construct.